A snapshot of research in learning technology - Rhona Sharpe (Association for Learning Technology, 2010)
The papers in this issue present a convenient snapshot of current research in learning technology, both in their coverage of the issues that concern us and the methods that are being used to investigate them. This issue shows that e-learning researchers are interested in: what technologies are available and explorations of their potential (Nie et al. explore the role of podcasting), how to design technology-mediated learning activities in ways which support specific learning outcomes (Simpson evaluates the role of ‘book raps' in supporting critical thinking), the identification of critical success factors in implementations (Cochrane's observation of three mobile learning projects) and how such e-learning initiatives can be sustained within an institutional context (Gunn's examination of the challenges of embedding ‘grass roots' initiatives). Finally e-learning research is concerned with investigating the impact of emerging technologies on education – in this case Traxler's discussion of mobile, largely student-owned, devices. Together these five papers demonstrate the scope of research in learning technology and it is with this in mind that we will soon be referring to this journal by its subtitle: Research in Learning Technology.